Magnetic Properties of the Tuxtuac Meteorite via 57Fe Mössbauer Spectroscopy - Cerón, María Luisa (2019)
It has been studied a sample of the Tuxtuac meteorite, which was classied as an ordinary chondrite. It was applied three analytical techniques. Thus, energy dispersive X-ray uorescence allowed us to identify iron, nickel and cobalt, which form the structure of the kamacite and taenite minerals. Likewise, X-rays diractometry allowed us to recognize the presence of the structural phases of the silicates olivine, pyroxene and orthopyroxene. Furthermore, 57Fe transmission Mössbauer spectroscopy indicated the presence of two magnetic sextets. One was assigned to troilite and the other, to goethite. After the magnetic separation process, this same technique was used to determine more detailed information about the magnetic minerals present in the sample. This resulted in other two magnetic sextets, which were assigned to kamacite and taenite, respectively. Besides, the presence of goethite in the sample may be the result of chemical weathering.